Sculpture with text: 'Dem Chor "Stem des Volks" Den Haag in Freundschaft gewidmet Chorvereinigung Anspach/Ts im Mai 1961' (1961)
Sculpture with text: 'Dem Chor "Stem des Volks" Den Haag in Freundschaft gewidmet Chorvereinigung Anspach/Ts im Mai 1961'.